A Grimm Warning : The Land of Stories #3 - Colfer, Chris, 1990-; Dorman, Brandon (New York ; Boston : Little, Brown and Company, 2014)
After thirteen-year-old Conner returns to the Land of Stories and reunites with his twin sister, Alex, who is training to become the next Fairy Godmother, war breaks out in the fairy-tale world.
Sequel to: The Land of Stories: the Enchantress returns.
Keywords: Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; War -- Fiction; Youths' writings; Fairy tales